A construção de conceitos sobre a pequenez humana : astronomia em aulas de filosofia no ensino médio - Nascimento, Carlos Alexandre do (2017)
This work analyzes the possibility that some of the contents of Astronomy would be introduced in Philosophy classes, verifying its applicability as a proposal for an interdisciplinary activity in high school. The aim of the project was to promote reflection and the creation of concepts with students about their own existence, the human condition on Earth and in the Cosmos. For this, a project was applied in seven classes for a first year high school group of the state school network, at the Francisco Gomes School, municipality of Cravinhos, state of São Paulo. The data was obtained through questionnaires, verbal and written reports and notes of the researcher. The acquisition of knowledge by students both in Astronomy and Philosophy contents is presented, as well as the analysis of this path, seeking the validation of the proposal, being the researcher the teacher of the class itself. The possible tangibility of Astronomy was a starting point to culminate in the inquiries and contents of Philosophy. It was found that both areas make it possible to think about the human condition, its smallness and other aspects related to the human being. In this way, it was verified that interdisciplinarity is possible, between the two convergent areas. A proposal of work in this way can become more attractive to the students, fostering the creation of concepts on the subject of the human being.